Effects of MgO addition on the phase, mechanical properties, and microstructure of zirconia-toughened alumina added with CeO2 (ZTA–CeO2) ceramic composite - Rejab, Nik Akmar; Ahmad Azhar, Ahmad Zahirani; Khoo, Seng Kian; Ratnam, Mani Maran; Ahmad, Zainal Arifin (Elsevier BV, 2014)
The effects of MgO addition on properties such as density, firing shrinkage, microstructure, Vickers hardness, and fracture toughness of ZTA–CeO2 ceramics composites were investigated. The amount of CeO2 used in the experiment was fixed at 5.0 wt% while the MgO addition was varied from 0 wt% to 2.0 wt%. Each composition was weighed, mixed, and pressed using hydraulic press under 300 MPa into 13 mm pellets. The pellets were sintered at 1600 °C for 4 h under pressureless condition. Vickers hardness and fracture toughness of the sintered samples were measured using the Vickers indentation method. Based on the SEM microstructures, elongated secondary phase, i.e. MgAl11CeO19, started to occur at 0.5 wt% MgO. This elongated phase was responsible for the increase in fracture toughness of the ceramic composites. Similarly, the addition of more than 0.5 wt% MgO produced another secondary phase (MgAl2O4), as detected by XRD. This phase was shown to have low intrinsic fracture toughness. Therefore, the sample with 0.5 wt% MgO showed the optimum properties with the highest fracture toughness (9.14 View the MathML source) and Vickers hardness (1591 HV) values.